Ultra-Low-Power CMOS Oscillator - Pedro Miguel Silva Machado (2021)
Currently, due to the constant technological advancement and search for innovation, the vast majority of the circuits that compose devices that we use in our day-to-day activities, have been decreasing in size. These are inserted in integrated circuits, where the area and energy consumption are major limitations. Also, a large number of applications and devices require a stable clock to operate correctly, being the use of an oscillator the most common solution to generate such frequency. Due to the current change, the conventional oscillator had to overcome changes in its design in order to keep up with the electronics industry. Such changes made oscillators in general less accurate compared to crystal oscillators, but more efficient in terms of energy, occupied area and cost. In this thesis, a very low consumption ring oscillator is presented, where it is intended to eliminate any external component that involves additional costs. One of the main challenges is the trade-off between the precision of the output frequency and energy consumption. Additionally, oscillators inserted in integrated circuits tend to suffer frequency deviations with PVT variations. The presented strategy involves building blocks that supply the oscillator with stable currents and voltages, in order to compensate for such variations. Designed using CMOS 0.18nm technology, it also includes a trimming circuit, making it possible to calibrate the process in post-fabrication.